Efficient Extraction of Bioenergy From Cinnamomum camphora Leaves - Zhang, Zanpei; Wu, Xuanxuan; Lai, Yong; Li, Ximei; Zhang, Dangquan; Chen, Yuanyuan (Frontiers in Energy Research, 2020)
Cinnamomum camphora is an evergreen tree native to China and distributed to some Asian countries. Its leaves are rich in bioactive compounds and their pharmacological effects are well-known. A potent method to extract and preserve the active biological substances is crucial for latter application in bioenergy and as chemical raw material. In this study, the metabolite profiles of C. camphora were comprehensively analyzed by using FT-IR and GC-MS after extracted by three type of solvent: ethanol, benzene, and acetone. The identified chemical compounds were then classified into different functional groups based on previous study. Our result proposes the potential application of C. camphora into biomedicine, bioenergy, and chemical raw materials industry.